A new strategy: Inhibitory effect and mechanism of Cymbopogon martinii essential oil on Aspergillus flavus. (February 2023) - Lin, Lizhen; Chen, Shuaipeng; Xia, Wenxin; Li, Tingting; Dong, Lin; Zhang, Yan; Zhang, Yuanyuan; Li, Hangying; Zhao, Yunsheng; Fu, Xueyan
Abstract: Cymbopogon martinii ( C. martini ) essential oil can inhibit the growth and toxin synthesis of Aspergillus flavus ( A. flavus ). In this study, C. martinii essential oil effectively inhibited radial growth, spore production, mycelium formation and aflatoxin B1 (AFB1 ) synthesis of A. flavus . It also significantly changed the morphology and ultrastructure of mycelium. C. martini essential oil significantly changed the activity of antioxidant enzymes and lipid peroxidation level in mycelium, and ROS level increased significantly. According to proteomic analysis, 1604 membrane proteins of A. flavus have been identified. C. martinii essential oil treatment seriously damaged the integrity of the A. flavus cell membrane, and C. martinii essential oil treatment has destroyed 58 cell membrane proteins and released 157 membrane proteins. This study provided a new explanation for the inhibition mechanism of C. martinii essential oil on A. flavus, and also provided technical support for the application of C. martinii essential oil in mildew prevention.